Southern Crucifix, Southern Cross : Catholic-Protestant Relations in the Old South - Stern, Andrew H. M., 1977- (Book collections on Project MUSE., 2012)
Southern Crucifix, Southern Cross examines the complex and often overlooked relationships between Catholics and Protestants in the antebellum South. In sharp contrast to many long-standing presumptions about mistrust or animosity between these two groups, this study proposes that Catholic and Protestant interactions in the South were characterized more by cooperation than by conflict.